(3GdJMaI GdTQjaI hGdWQaI GdefjaIs - (3GdLhGfj , TQa GdOjf CHh Ydj eMeO Hf CSYO Hf Ydj Hf eYeQ GdTQja GdMSjfj GdYdhj GdYHjOj GdeGdcj, GdLhGfj,J (B588 (3g` s
(3ChdgG (B:s
(3jHJOF HPcQ hdOg s
(3fSNI edhcjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B31 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B49s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B626 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B83 s
Keywords: (3GdJGQjNs